2014
DOI: 10.1088/0964-1726/23/11/117005
|View full text |Cite
|
Sign up to set email alerts
|

Medium to long term behavior of MR dampers for structural control

Abstract: The medium to long term behavior of a prototype magnetorheological (MR) damper for structural control of earthquake induced vibrations is investigated herein. Unlike some applications for which MR devices experience frequent dynamic loads, seismic dampers might not be used for most of their life, staying dormant for a long period until an earthquake hits the hosting structure. This work aims to evaluate the effectiveness of a MR damper after years of inactivity. A MR device has been tested twice, first in 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The authors tried to associate the variations of the mechanical behavior to the most probable physical modifications in MR fluids. Figure 1 shows one of the prototypes full-scale MR dampers which were studied during a wide experimental campaign performed in 2008 and in 2013 [3], and were finally experimentally tested in July 2017. The intensity of the feeding current is in the range 0÷3 A and the maximum force, that can be developed at the maximum current intensity, is of about 30 kN.…”
Section: Ten Years Ageing Experimental Campaign On Prototype Mr Dampersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors tried to associate the variations of the mechanical behavior to the most probable physical modifications in MR fluids. Figure 1 shows one of the prototypes full-scale MR dampers which were studied during a wide experimental campaign performed in 2008 and in 2013 [3], and were finally experimentally tested in July 2017. The intensity of the feeding current is in the range 0÷3 A and the maximum force, that can be developed at the maximum current intensity, is of about 30 kN.…”
Section: Ten Years Ageing Experimental Campaign On Prototype Mr Dampersmentioning
confidence: 99%
“…On the contrary, in earthquake engineering applications, MR devices might be called to give a few seconds long effective response after years of quiescence. The authors [3], after a ten years long campaign, present and discuss the most important experimental results aimed to show the evolution over time of response promptness, dissipating capability, and force reaction of MR dampers.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, after a period of inactivity, MR dampers can exhibit a singular start-up phase in which they provide reduced forces. Some MR dampers need a number of cycles before settling and delivering a uniform response and their distinctive hysteretic loop [33]. This is due to an initial nonhomogeneous distribution of the microparticles inside the MR fluid.…”
Section: Processing and Control Logic Phasementioning
confidence: 99%
“…With more and more applications of MR dampers in engineering practices, the durability of MR dampers, which are closely related to the particle sedimentation, the fluid thickening, the particle oxidation, and the seal wearing attracts growing attentions. Some studies on the durability of MR damper have been conducted through investigating the sedimentation ratio of MR fluids, the temperature‐induced effect of MR fluids, the change of dynamic viscosity and the yield stress of MR fluids, the oxidation of MR fluid particles, and the wearing resistance of seal materials . Recently, Caterino et al investigated the medium and long‐term behavior of a prototype MR damper after a 5‐years' storage, and the results showed that the damping capacity of the prototype MR damper did not change too much compared with the data measured 5 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on the durability of MR damper have been conducted through investigating the sedimentation ratio of MR fluids, the temperature‐induced effect of MR fluids, the change of dynamic viscosity and the yield stress of MR fluids, the oxidation of MR fluid particles, and the wearing resistance of seal materials . Recently, Caterino et al investigated the medium and long‐term behavior of a prototype MR damper after a 5‐years' storage, and the results showed that the damping capacity of the prototype MR damper did not change too much compared with the data measured 5 years ago. However, the damping performance of the used MR dampers, which have been in a long‐term engineering service, has not been reported, to the authors' best knowledge.…”
Section: Introductionmentioning
confidence: 99%